2022
DOI: 10.3390/life12091320
|View full text |Cite
|
Sign up to set email alerts
|

Controllable and Uncontrollable Stress Differentially Impact Fear Conditioned Alterations in Sleep and Neuroimmune Signaling in Mice

Abstract: Stress induces neuroinflammation and disrupts sleep, which together can promote a number of stress-related disorders. Fear memories associated with stress can resurface and reproduce symptoms. Our previous studies have demonstrated sleep outcomes can be modified by stressor controllability following stress and fear memory recall. However, it is unknown how stressor controllability alters neuroinflammatory signaling and its association with sleep following fear memory recall. Mice were implanted with telemetry … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 122 publications
1
8
0
Order By: Relevance
“…Social interaction appears to be linked to learning and is evolutionarily conserved across taxonomic classes. The hippocampus is a key region for both memory and sleep [ 32 , 33 ], and stress and/or stress-induced changes in sleep, can both alter the processing of new information [ 34 ] and the retrieval of previously acquired memories [ 35 ]. This evidence supports our observed learning impairment in the SI animals during the beginning of the BB task, and it is plausible that the increased stress sensitivity of the SI vulnerable animals led to a greater learning impairment, as stress can alter hippocampal morphology and induce synapse loss within the hippocampus [ 36 , 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…Social interaction appears to be linked to learning and is evolutionarily conserved across taxonomic classes. The hippocampus is a key region for both memory and sleep [ 32 , 33 ], and stress and/or stress-induced changes in sleep, can both alter the processing of new information [ 34 ] and the retrieval of previously acquired memories [ 35 ]. This evidence supports our observed learning impairment in the SI animals during the beginning of the BB task, and it is plausible that the increased stress sensitivity of the SI vulnerable animals led to a greater learning impairment, as stress can alter hippocampal morphology and induce synapse loss within the hippocampus [ 36 , 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…In a study using NanoString® panels that assessed multiple immune pathways, we found that contextual fear memories associated with ES resulted in a down-regulation in HPC of many genes associated with neuroinflammation and an up-regulation of genes associated with neuroprotection ( Adkins et al, 2022 ) (see Fig. 4 ).…”
Section: Animal Models Of Fear Memorymentioning
confidence: 99%
“…IS showed up-regulation of genes involved in cytokine signaling (Tnfrsf25, p = 0.013); activation of the innate immune response (Lcn2, p = 0.0132); recruitment of neutrophils (Lcn2, p = 0.0132 and Ncf1, p = 0.0149); and the Arc gene. Adapted from Adkins et al, (2022) . …”
Section: Animal Models Of Fear Memorymentioning
confidence: 99%
“…In fact, controllable events might even promote control over unpredictable events 153 and produce differential HPA activation or immune profiles. 154 , 155 Interestingly, voluntary exercise can be seen as a controllable event that produces several changes to the BBB and GB ( Figure 3 ). A better understanding of the impact of physical exercise on these barriers could help its promotion in the context of mental health or other conditions.…”
Section: Distinct Environmental Features Differentially Modulate Biol...mentioning
confidence: 99%